The Seasonal Incidence of Slipped Capital Femoral Epiphysis: A Systematic Review and Meta-Analysis - Carter J. K. White; Jacob D. Kodra; Harshavardhan Bollepalli; Kai Yang; Scott E. Van Valin; Xue-Cheng Liu (Children, 2025)
Background/Objectives: Slipped capital femoral epiphysis (SCFE) is a common adolescent hip disorder characterized by the posterior and inferior slippage of the femoral head through the growth plate. This study aimed to assess seasonal trends in the incidence of SCFE above 40° N latitude using cosinor regression analysis. Methods: A systematic review was conducted following Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines and registration in Prospero. A keyword search of PubMed, Scopus, Web of Science, and Ovid was conducted using terms related to SCFE and seasonal or monthly variation. Studies were included if they reported month-by-month SCFE incidence in pediatric populations. Studies were excluded if they had duplicated population cohorts. Data from studies conducted above 40° N were extracted for cosinor regression analysis. Quality assessment was performed using the JBI Critical Appraisal Checklist for Studies Reporting Prevalence Data. Results: A total of seventeen studies were included, amassing a total of 21,428 children analyzed. Six investigations reported monthly incidence data for populations > 40° N. The highest pooled monthly incidence was observed in August (482 cases). Alternatively, February was the month with the lowest SCFE incidence (293). Cosinor regression analysis demonstrated that SCFE occurs more frequently during early summer and fall months (p < 0.0001). Conclusions: SCFE incidence follows a significant seasonal trend in higher-latitude (>40° N) populations, with a consistent late-summer peak. Recognizing seasonal variation patterns may inform early diagnosis and intervention in SCFE, improving outcomes in pediatric physeal injuries.